2017
DOI: 10.1155/2017/1270608
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Talc Increases the Risk of Lung Cancer: A Meta-Analysis of Occupational Cohort Studies

Abstract: Objective Talc is widely used in industrial applications. Previous meta-analyses of carcinogenic effects associated with inhaled talc included publications before 2004, with a lack of data in China, the largest talc-producing country. The safety of workers exposed to talc was unclear due to limited evidence. The objective of this study was to reevaluate the association between inhaled talc and lung cancer. Setting, Participants, and Outcome Measures A meta-analysis was performed to calculate the meta-SMR of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Therefore, when physicians coadminister sirolimus and anti-tuberculosis drugs, they should individually increase the dose of sirolimus under close monitoring of the plasma levels. In our case series, no patient received talc pleurodesis, considering that previous studies have demonstrated that exposure to talc may increase the risk of lung cancer [ 11 , 12 ]. Therefore, autologous blood or hypertonic glucose is used as a sclerosing agent for chemical pleurodesis in many hospitals in China because of the low medical risk associated with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when physicians coadminister sirolimus and anti-tuberculosis drugs, they should individually increase the dose of sirolimus under close monitoring of the plasma levels. In our case series, no patient received talc pleurodesis, considering that previous studies have demonstrated that exposure to talc may increase the risk of lung cancer [ 11 , 12 ]. Therefore, autologous blood or hypertonic glucose is used as a sclerosing agent for chemical pleurodesis in many hospitals in China because of the low medical risk associated with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis for asbestos contamination showed no significant difference in lung cancer deaths between participants exposed to talc, with and without asbestos ( p = 0.8680), indicating that this confounding factor may have no significance. They concluded that it is necessary to evaluate the safety of workers with occupational talc exposure . An interesting point of this report is that considerable regional differences existed in the incidence of lung cancer among talc workers.…”
Section: Discussionmentioning
confidence: 82%
“…They concluded that it is necessary to evaluate the safety of workers with occupational talc exposure. 12 An interesting point of this report is that considerable regional differences existed in the incidence of lung cancer among talc workers. They evaluated meta-analysis data from three regions: Asia, Europe and North America.…”
Section: Discussionmentioning
confidence: 88%
“…Studies of Yamada et al [19] suggested a correlation between fibrous talc and female lung cancer. A recent study suggested a correlation between talc exposure and lung cancer regardless of whether asbestos is present at detectable levels [20].…”
Section: Discussionmentioning
confidence: 99%